Multi-Omics Analysis of Chronic Heat Stress-Induced Biological Effects, Liver Injury, and Heat Tolerance Mechanisms via Oxidative and Anti-Inflammatory Pathways in Early-Pregnancy Sows - Jie Chai; Zhenhao Wen; Li Chen; Qiang Pu; Taorun Luo; Xiaoqian Wu; Zihan Ma; Zonggang Luo; Jia Luo; Jingyong Wang (Antioxidants, 2025)
The prenatal environment critically influences sow and offspring health, with the liver being highly susceptible to heat stress (HS) and vital for antioxidant defense. However, mechanisms underlying HS impacts on early pregnancy and hepatic adaptation remain unclear. This study applied multi-omics to analyze chronic HS responses in early-pregnancy sows. Results demonstrated that HS reduced blood oxygen (PO2) and basophils while elevating red blood cell parameters (RBC, HGB, and HCT). Endocrine disruptions included upregulated adrenal hormones (ACTH and cortisol) and suppressed thyroid (T3 and TSH) and reproductive hormones (LH1 and FSH). Liver dysfunction was evident through elevated biomarkers (AST, ALT, and TBIL) and pro-inflammatory IL-6, coupled with reduced anti-inflammatory IL-10. HS induced oxidative stress, marked by increased total antioxidant capacity (T-AOC) but decreased SOD and MDA levels. Liver tissue exhibited apoptosis (Bax/CD8 upregulated and Bcl-2 downregulated) and upregulated heat shock proteins (HSP70/90). Multi-omics analysis demonstrated that under heat stress conditions, the pyrimidine metabolism, oxidative phosphorylation, and tryptophan metabolism pathways were significantly upregulated in the liver. This upregulation may be mediated by key metabolites, including AMP, NAD, and UMP. These metabolites likely contribute to the body’s adaptation to heat stress. Chronic HS impaired liver function and anti-inflammatory responses but triggered compensatory antioxidant and metabolic reprogramming. These findings underscore the liver’s dual characteristics of vulnerability and resilience under high-temperature stress, offering valuable mechanistic insights that can inform strategies to enhance heat tolerance in pregnant sows.